2005
DOI: 10.1088/0031-9155/50/9/014
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaco-thermodynamics of deuterium-induced oedema in living rat brain via1H2O MRI: implications for boron neutron capture therapy of malignant brain tumours

Abstract: In addition to its common usage as a tracer in metabolic and physiological studies, deuterium possesses anti-tumoural activity and confers protection against gamma-irradiation. A more recent interest in deuterium emanates from the search for alternatives capable of improving neutron penetrance whilst reducing healthy tissue radiation dose deposition in boron neutron capture therapy of malignant brain tumours. Despite this potential clinical application, deuterium induces brain oedema, which is detrimental to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…[1] iron term for most brain regions, the field dependence of brain 1 H 2 O R 1 primarily arises from the B 0 dependence of r 1M . In other work involving in vivo 2 H‐substitution titration rodent studies (44), we found that an increasing 2 H proportion increases 1 H 2 O T 1 not only because the less competent 2 H replaces 1 H, but also because it induces cerebral edema and thus decreases f M .…”
Section: Discussionmentioning
confidence: 59%
“…[1] iron term for most brain regions, the field dependence of brain 1 H 2 O R 1 primarily arises from the B 0 dependence of r 1M . In other work involving in vivo 2 H‐substitution titration rodent studies (44), we found that an increasing 2 H proportion increases 1 H 2 O T 1 not only because the less competent 2 H replaces 1 H, but also because it induces cerebral edema and thus decreases f M .…”
Section: Discussionmentioning
confidence: 59%
“…Since most of the toxic effects are centralized in neuronal tissue, toxic effects upon direct contact with the retinal cells are possible. It has been shown that mammals can tolerate a concentration of up to 30 % of D2O in drinking water, and that a short exposure to a blood serum deuterium fraction of up to 0.23 ml/ml seems to be safe [14][15][16][17][18]. The tested concentration in this study is 0.13 ml/ml.…”
Section: Introductionmentioning
confidence: 82%
“…One method to ameliorate the attenuation problem is to change the water composition from normal water to deuterated water (also referred to as heavy water) (Slatkin, Stoner et al 1983;Nakagawa, Hatanaka et al 1994;Kushner, Baker et al 1999;Medina, Li et al 2005). Studies have shown that approximately 20% of total body water (TBW) can be replaced with deuterated water without deleterious effects (Kushner, Baker et al 1999).…”
Section: Medical Applications Of Neutron Imagingmentioning
confidence: 99%